2015
DOI: 10.1097/hp.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Thyroid 131I Activity of Five Human Subjects Exposed to a Radioactive Plume at Tamura City in Fukushima

Abstract: Thyroid 131I activities were determined for five human subjects from a disaster medical assistance team of Fukui Prefectural Hospital. The team was dispatched to the Tamura City Sports Park, 40 km from the Fukushima Daiichi nuclear power plant. They were exposed to a radioactive plume on 15 March 2011. In vivo measurements at Fukui Prefectural Hospital were conducted around 17 h after the team left the park. A thyroid counter equipped with a 51-mm-diameter × 51-mm-thick NaI(Tl) detector with a 20-mm-thick lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…In addition, the results of the assessment with environment monitoring, at the same time and in the same place, are invaluable for evaluating radiation doses in the general population after nuclear accidents, and occasionally provides important and fundamental information about the intake of biokinetic radionuclides. Indeed, we previously reported that the thyroid iodine-131 ( 131 I) activities derived from thyroid counter measurements were in good agreement with environment monitoring data, the results also implied a faster kinetics of iodine metabolism in younger adults as previously suggested by Hänscheid et al [ 1 , 2 ].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, the results of the assessment with environment monitoring, at the same time and in the same place, are invaluable for evaluating radiation doses in the general population after nuclear accidents, and occasionally provides important and fundamental information about the intake of biokinetic radionuclides. Indeed, we previously reported that the thyroid iodine-131 ( 131 I) activities derived from thyroid counter measurements were in good agreement with environment monitoring data, the results also implied a faster kinetics of iodine metabolism in younger adults as previously suggested by Hänscheid et al [ 1 , 2 ].…”
Section: Introductionsupporting
confidence: 88%
“…The whole body counter measurements of five men of a six-member team that comprised the second disaster medical assistance team (DMAT) of Fukui Prefectural Hospital were used in the current study. The details of the subjects were described previously [ 2 ]. In short, four of five men ingested stable iodine pills, a total of 100 mg of potassium iodide, as prophylaxis for internal exposure at 02:30 on 14 March 2011.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have also been a few other reports related to direct measurements of 131 I [14][15][16]; however, the number of subjects examined in each study was very limited. Thus, regarding the general public, the number of people for whom data are available is only about 1,300 in total, which is much less than the number of persons whose thyroid doses should be carefully evaluated (e.g., children, pregnant women, delayed evacuees).…”
Section: Jrprmentioning
confidence: 99%